Spatial memory deficits after vincristine-induced lesions to the dorsal hippocampus. - Daniela M Meléndez; Rebecca E Nordquist; Louk J M J Vanderschuren; Franz-Josef van der Staay (PLoS ONE, 2020)
Vincristine is a commonly used cytostatic drug for the treatment of leukemia, neuroblastoma and lung cancer, which is known to have neurotoxic properties. The aim of this study was to assess the effects of vincristine, injected directly into the dorsal hippocampus, in spatial memory using the spatial cone field discrimination task. Long Evans rats were trained in the cone field, and after reaching training criterion received bilateral vincristine infusions into the dorsal hippocampus. Vincristine-treated animals presented unilateral or bilateral hippocampal lesions. Animals with bilateral lesions showed lower spatial working and reference memory performance than control animals, but task motivation was unaffected by the lesions. Working and reference memory of animals with unilateral lesions did not differ from animals with bilateral lesions and control animals. In sum, intrahippocampal injection of vincristine caused profound tissue damage in the dorsal hippocampus, associated with substantial cognitive deficits.